Bioclimatic double-skin facades - Bonham, Mary Benedict (New York : Routledge, 2020)
"Visually enriched with over 250 photographs and drawings, Bioclimatic Double-Skin Façades is an essential reference guide for understanding the types and functions of double-skin facades. Author Mary Ben Bonham examines the history and continuing potential of double-skin architecture, informing on the variety of approaches possible and advising a rigorous integrated design process leading to application. Featuring a wide selection of architectural examples, the book will be of interest to professionals and students within the fields of architecture, engineering, and construction. Characterized by a buffer-like air space between two glazed building skins, double-skin windows and facades aim to improve building comfort and energy performance. Double skins introduce complexity and initial costs, yet significant buildings in locations around the globe continue to select this approach. In addition to exploring motivations, benefits, and cautions for designing with double skins, the book provides a primer on fundamental facade design concepts and strategies for control of thermal, luminous, and acoustic environments. Chapters also address alternative types of high-performance facades and implications for each phase of facade design and construction. Bioclimatic Double-Skin Facades promotes bioclimatic design that is inspired by nature, measured in performance, and uniquely adapted to climate and place. In-depth case studies illustrate how double-skin facades have been adapted to a range of climates and cultural settings: Marseille Library and Grenoble Courthouse in France, Cambridge Public Library in Massachusetts, Manitoba Hydro Place in Canada, and the Pearl River Tower in China"--
OCLC-licensed vendor bibliographic record.
Keywords: Exterior insulation and finish systems; Facades -- Design and construction; Bioclimatology; ARCHITECTURE / Design & Drafting; ARCHITECTURE / General